Regional financial cooperation - Ocampo, José Antonio (United Nations Economic Commission for Latin America and the Caribbean ; Brookings Institution Press, 2006)
"Assesses how regional financial institutions can help developing countries, often at a disadvantage within the global financial framework, finance their investment needs, counteract the volatility of private capital flows, and make their voices heard"--Provided by publisher.